2019
DOI: 10.1097/phm.0000000000001012
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix and Adhesion Molecule Gene Expression in the Normal and Injured Murine Intervertebral Disc

Abstract: This is the first study to examine the relative expression of 84 genes in normal mouse NP and AF. Key genes in the normal and injured mouse IVDs was confirmed with real-time PCR. This information should be useful for studying the mouse model of IVD degeneration, and guide future cell therapy approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Briefly, the NP tissue organs were isolated from the NP region of IVDs in the spinal column from the first lumbar spine to the tenth tail region 23 . The dissected NP tissues were briefly rinsed in sterile PBS and immediately placed in 6‐well cell culture plates containing culture medium (10% FBS in αMEM with penicillin and streptomycin).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the NP tissue organs were isolated from the NP region of IVDs in the spinal column from the first lumbar spine to the tenth tail region 23 . The dissected NP tissues were briefly rinsed in sterile PBS and immediately placed in 6‐well cell culture plates containing culture medium (10% FBS in αMEM with penicillin and streptomycin).…”
Section: Methodsmentioning
confidence: 99%
“…These investigators used a model of joint inflammation induced by a combination of collagen and LPS 24 , which likely induced autoantibodies to various collagen epitopes, as well as activating the innate immune system with LPS. In the tail IVD injury model, there is loss of intradiscal pressure immediately following injury, and subsequent NP cell dissociation 35 with loss of N-cadherin 35 , 39 . These findings highlight the complexities of inflammation pathways, both in synovial joints and IVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar and coccygeal NP and AF tissues were pooled for each animal. Specifically, the gelatinous NP was scraped off with a scalpel 39 . AF tissues, identified by their concentric rings, were shaved off the cartilaginous endplate with a scalpel.…”
Section: Methodsmentioning
confidence: 99%
“…Cell type-specific markers have been proposed either by focusing on specific candidate genes or classes in human primary cells [21][22][23][24][25] and animal models, [25][26][27][28][29] or by using unbiased whole transcriptome approaches. [30][31][32][33][34][35][36][37][38][39] Although these studies have identified a common subset of markers that have helped to define IVD cell phenotypes, their findings also highlight differences across species.…”
Section: Introductionmentioning
confidence: 99%
“…17 Prepare StageTips by punching 12 discs of C18 using an 18-gauge needle and packing a 200 μL StageTip.F I G U R E 4 Schematic overview of workflow for proteomics and metabolomics. A, Proteomic workflow including homogenization (protein extraction steps 1-7), protein isolation (sample preparation steps 1-10), protein digestion (sample preparation steps[11][12][13][14][15], fractionation (sample preparation steps[16][17][18][19][20][21][22][23][24][25][26][27][28], and the mass spectrometry instrument. B, Metabolomic workflow including homogenization (metabolite extraction steps 1 and 2), metal bead removal (metabolite extraction steps 3-7), addition of internal standards (sample preparation steps 1-10), validation run (metabolite validation steps 1-7), and the mass spectrometry instrument Place tips into centrifuge and add 50 μL ACN to each tip and centrifuge at 10 000 RCF at RT for 2 minutes.…”
mentioning
confidence: 99%